2021
DOI: 10.1210/jendso/bvab048.1983
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Thyroiditis Post COVID-19 Infection

Abstract: Thyroid tuberculosis (TT) is a rare disease and can be a diagnostic challenge. Here we highlight a case of TT following COVID-19 infection. A 38-year Myanmar immigrant female presented with nocturnal fever, fatigue, nausea, sore throat, appetite and weight loss for 1 week with dysphagia, neck swelling, dyspnea, and watery diarrhea. Medical history included renal transplant due to ESRD from IgA nephropathy, DM and treated latent TB with no prior or family history of thyroid disease. She had COVID 7 months ago, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Then, the remaining 2337 studies were screened by title and abstract. Full-text screening was conducted for 23 studies, and finally, data were extracted from 21 studies comprising [11][12][13][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] 33 individual cases (Fig 1). The studies were reported from 13 countries with the highest frequency from the United States of America (10 patients), and Tu ¨rkiye (eight patients) followed by Bangladesh (three patients), and Mexico (three patients).…”
Section: Resultsmentioning
confidence: 99%
“…Then, the remaining 2337 studies were screened by title and abstract. Full-text screening was conducted for 23 studies, and finally, data were extracted from 21 studies comprising [11][12][13][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] 33 individual cases (Fig 1). The studies were reported from 13 countries with the highest frequency from the United States of America (10 patients), and Tu ¨rkiye (eight patients) followed by Bangladesh (three patients), and Mexico (three patients).…”
Section: Resultsmentioning
confidence: 99%